Motivations of Marathoners by socio demographic and training variables - Antonio Zarauz Sancho; Francisco Ruiz-Juan (FEADEF, 2013)
in the growing population of Spanish and Mexican route runners we analyze their main motivations for running and their main bio-socio-demographic characteristics. It also analyzes the influence on the score of these variables in each of the motivational subscales in both Spanish as in Mexican route runners sample. This gives valuable data describing their motivations and socio-demographic characteristics and training, and concludes that in the Mexican sample route runners were obtained significantly higher scores than in the Spanish in each of the motivations for running analyzed . Moreover, the two motivations accounted for both samples are the most self-determined (meaning of life, self-esteem and health orientation) and least valued was the least self-determined (recognition). Also that in bio-socio-demographic characteristics of the Mexican sample, there are many significant differences by gender, while the Spanish sample there are only on primary work activity and BMI. Finally, the influence of biological variables sociodemographic scores on each of the motivational subscales analyzed, there are many significant differences, both by gender and between Spanish and Mexican samples.